A theory of the relationship between foreign direct investment and trade - José Pedro Pontes (European Regional Science Association (ERSA), 2004)
Although empirical evidence shows that the relationship between foreign direct investment (FDI) and trade is complex, theories of international investment (both vertical and horizontal) present simple patterns of relation. By allowing for different locations of vertically-related stages of production and distinguishing between trade in finished goods and trade in intermediate goods, this paper introduces a non monotonic relationship between multinational firms and trade costs, which must be neither too high nor too low for FDI to arise. Exports and FDI be have as complements for high levels of trade costs and as substitutes otherwise. J.E.L. Classification: F23, F12, C72. Keywords: Foreign Direct Investment, Multinationals, Trade, Intermediate Goods, Non cooperative Games.
Keywords: 330; Foreign Direct Investment; Multinationals; Trade; Intermediate Goods; Non cooperative Games